Relativismus dolní i horní hranice aktivního trampování nositelů české trampské subkultury - Altman, Karel (Studia Etnologiczne i Antropologiczne, 2022)
The bearers of Czech tramping, which arose more than a century ago and has undergone an extremely remarkable development, have always been primarily young men, to a lesser extent female. Their active hiking had lower and upper boundaries. While the lower limit was relatively strictly determined by reaching the age of majority, that is to say,the age of fifteen, the upper limit (that is, thepartial or definitive end of tramping activity and affiliation with the tramp community) was rather relative. The study focuses on covering the range of these cut-off points of active tramping, which were mostly identical to major life milestones (entry into basic military service, starting a professional career, entry into marriage, parenthood, or even death).